PLM, process, practice and provenance: knowledge provenance in support of business practices in Product Lifecycle Management. (20th August 2008) - Grieves, Michael W.; Tanniru, Mohan
Structured information supports processes, but practices require unstructured, contextual and tacit knowledge. However, acquiring information system based tacit knowledge used in decision-making has been a major challenge in the last three decades. This task became even harder as technology enabled firms, especially manufacturing began to distribute their operations globally and in turn also globally distributed their decision makers. Product Lifecycle Management (PLM) involves many practices as well as processes. Singularity, cohesion and cued availability are some of the unique characteristics of these practices. Start and smart parts and Virtual Collaboration Rooms are some prevalent approaches used to address these practices. In this article, a knowledge provenance framework is used to develop a broader approach to elicit and structure some of the knowledge associated with these practices and is illustrated with an example.